2021
DOI: 10.33545/gynae.2021.v5.i5b.1024
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcomes in the first wave of COVID-19 infected pregnant women

Abstract: The COVID-19 pandemic continues to be a rapidly evolving situation with limited data on its impact on pregnancy. The study was conducted to evaluate the maternal and perinatal outcomes of pregnant women in the first wave of COVID-19 infection Materials and Methods: Clinical records were retrospectively reviewed for 129 pregnant women with laboratory confirmed COVID-19 infection admitted in the Department of Obstetrics and Gynecology, Regional Institute of Medical Sciences, Imphal (Manipur, India) from 27 th Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Maternal mortality rate in our study was 6.7%, while it was found to be 11% in a study by Kanhere et al, Kanwar et al reported this as 12%, Siddiq et al of 9.7%, while Devi et al reported no mortality in their studies. 4,[7][8][9] There were no significant differences noted between total and subtotal in terms of maternal or delivery characteristics. Subtotal hysterectomy was easy to perform but has a rare risk of development of cancer cervix and it has no role in cases of placenta previa or adherent placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal mortality rate in our study was 6.7%, while it was found to be 11% in a study by Kanhere et al, Kanwar et al reported this as 12%, Siddiq et al of 9.7%, while Devi et al reported no mortality in their studies. 4,[7][8][9] There were no significant differences noted between total and subtotal in terms of maternal or delivery characteristics. Subtotal hysterectomy was easy to perform but has a rare risk of development of cancer cervix and it has no role in cases of placenta previa or adherent placenta.…”
Section: Discussionmentioning
confidence: 99%